Genealogi arsitektur modern Indonesia - Johannes Adiyanto (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2020)
Architectures in Indonesia are often identified as 'unique' compared to European and American constructions. They are referred to as Wastuwidya by Mangunwijaya and Nusantara by Prijotomo. This paper, therefore, aimed to examine the reasons for the perceived similar principles between the Indonesian architectures and those in Europe or America and also reviewed the architecture in the country beyond the identity. This involved the application of a historical approach with synchronous-diachronic methods to determine the significance of a historical timeline and its architectural content. The results showed the country’s modern architecture is associated with the foreign entry, its climate, and socio-cultural conditions, and also perceived as a sign of certain political powers presented during the Daendels and Sukarno era. Indonesian and European/American architectural designs were also observed to have different entry processes. Therefore, modern architecture should be perceived as a process rather than a product. © 2020 Johannes Adiyanto